Critical Thinking on Social Studies Learning for Elementary School Students - Rohmat Nugraha Sasmita; Sapriya Sapriya; Enok Maryani (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This research is motivated by the importance of critical thinking skills in students. Critical thinking skills are important abilities that must be possessed in the 21st century. Critical thinking skills are an important aspect that students must have to face the challenges of modern life. therefore it is necessary to have learning for students who are oriented toward students critical abilities. For this reason, in this study, researchers focused on examining the development of critical thinking learning in social science subjects at the elementary school level. The purpose of this study was to analyze the importance of learning to think critically in elementary school students, especially in social studies learning. This study uses qualitative methods by collecting data through interviews and observation. the data obtained was then analyzed qualitatively. This study shows the importance of teachers in developing models and innovating learning in the classroom to improve critical abilities in elementary school children. teachers have an important role to facilitate learning so that children can have a critical attitude.